Guide to nominating and learning from Best Practices in improving environments (Habitat II Secretariat NairobiKE, 1996)
Provides a framework for identifying, nominating and documenting BEST PRACTICES as a means of learning from past and ongoing successes and as an essential step to preparing the National Plan of Action.
DC